Temporal-spatial perception adjustment to fitness enhances the cooperation in the spatial prisoner’s dilemma game - Ying, Xinyue; Wang, Jingrui; Jin, Xing; Wang, Chao; Zhang, Zhouyang; Wang, Zhen (Frontiers in Physics, 2023)
The exploration of real-world cooperative behavior is essential for societal development. In real life, the surrounding social environment and past experiences often influence individuals' assessment of their self-fitness. Based on this phenomenon, we propose a novel model that explores the effect of subjective human perceptions on the evolution of cooperation, combining temporal and spatial dimensions into individual fitness. In this model, strategy persistence is used as a proxy for the temporal dimension. Strategy popularity, on the other hand, is portrayed to characterize the subjective influence of the spatial dimension. The weight distribution between the temporal perception and the spatial perception can be controlled by the parameter α, and the intensity of the subjective perception can be regulated by the parameter β. Based on the experiment, we find that when spatial perception is fully considered, the system tends to reach a fully cooperative state via network reciprocity. Conversely, fully considering the temporal state allows some cooperators to maintain cooperative behavior even under more unfavorable conditions (i.e., larger temptation). Notably, an intermediate state α exists when both temporal and spatial perceptions are considered, resulting in a higher level of cooperation compared to α = 0 or 1. Micro-analysis of the evolution of cooperation in temporal or spatial perception reveals the mechanism of macroscopic phenomena. Additionally, the robustness of the mechanism is explored by varying the intensity of subjective perception β and the upper limit of strategy age A_max. Similarly, we explore the validity of our work to different network structures, the different numbers of agents, and the real social network. Overall, this study contributes to understanding the impact of individual subjective factors, such as temporal-spatial perception, on the evolution of cooperation in society.